Reconstructing Islamic Financial Management Philosophy through a Dynamic Maqashid al-Shariah Framework - Liya Setiawati; Muhardi Muhardi (International Forum of Researchers and Lecturers, 2026)
The last few decades of the institutionalization of Islamic finance are notable for the fundamental controversies surrounding its institutionalization. These controversies can be seen rooted in the dual phenomena of the legalistic form taking Islamic finance as a practice and the overwhelming reliance on modern managerial paradigms. There are significant ethical gaps as consequence. The objective of the current research is to aim to help reconstruct the philosophy of Islamic financial management from the perspective of the maqasid al-shariah and, importantly, to treat it as a primary lens and not secondary. The research employs a qualitative conceptual and philosophical approach and attempts to engage the prevailing paradigms and contours of Islamic finance through the lenses of ontology, epistemology and axiology. The research finds that contemporary Islamic financial management suffers from a deficient ontology of profit, epistemology of compliance and an axiology that is instrumentally weak. In light of the above, the research articulates the philosophy of Islamic Finance in the direction of the maqasid and posits that finance as an instrument of maslahah, and so, in that order, integrate revelation, reason, and the socio-economic order, and it is, thereby, just to place the preeminent values of human dignity, justice and the welfare of the greater good (public) in the financing of maslahah. The research articulates a coherently formulated philosophy of Islamic financial management based on the maqasid for the Islamic financial management of practice and for empirical, policy and institutional Islamic finance reform, and so makes a significant theoretical contribution.